A checklist for the zooplankton of the Middle Xingu – an Amazon River system - SAC. Brito; M. Camargo; NFAC. Melo; RA. Estupiñan (Brazilian Journal of Biology)
Abstract A zooplankton checklist is presented for the Middle Xingu River, based on surveys conducted at four sites in the main channel and two fluvial lakes. A total of 175 taxa are listed, including 141 rotifers, 20 cladocerans, and five copepods. Rapids presented the greatest species richness, with up to 124 taxa, while Ilha Grande lake had 70 taxa, the lowest number. Non-planktonic benthic larvae were recorded frequently in the samples.